Pengembangan Video Animasi pada Materi Keragaman Suku Bangsa dalam Pembelajaran Ilmu Pengetahuan Sosial di Kelas IV Sekolah Dasar - Siska, Yulia; Manalu, Okta Lusiana; Wicaksono, Andri (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
This research aims to develop, test the feasibility, effectiveness and response of students and teachers to audio-visual media in the form of learning animations on ethnic diversity material. The background for conducting this research is that there is no learning media in the form of animated videos, learning does not use a variety of media, and learning resources are student environment oriented. This research uses a development design with the ADDIE model which involves five steps including: Analyze, Design, Development, Implementation, and Evaluate. The data analysis technique used is descriptive and quantitative analysis in the form of validity tests, product trials, and final product tests (t tests). The research results obtained from the validity test of material experts were 83%, language experts were 100%, and media experts were 79%. The results of product trials on students were 88% and the response from educators was 88%. The results of the t test on the pre-test and post-test values showed (12.29) > t-table (1.83). This means that the animated video media developed is effectively used in the learning process.